1987
DOI: 10.1039/p19870000699
|View full text |Cite
|
Sign up to set email alerts
|

Lewis acid-promoted conjugate reduction of α,β-unsaturated carbonyl compounds by 2-phenylbenzothiazoline (2-phenyl-2,3-dihydrobenzothiazole)

Abstract: Reduction of various a,P-unsaturated ketones ( 3 a -g ) and (4a-4) in methanol by the benzothiazoline (1) in the presence of aluminium chloride gives, in all cases, the corresponding saturated ketones ( 5 a -g ) and (6a-d) without any of the unsaturated or saturated alcohol. Reduction of a,P-unsaturated esters (7a,b) similarly gives the saturated esters (9a,b), while reaction of cinnamaldehyde (8) with compound (1) does not occur at all. Among the Lewis acids examined, aluminium chloride gives the best results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(15 citation statements)
references
References 2 publications
0
15
0
Order By: Relevance
“…[56] 3-Phenyl-1-(2-pyridyl)propan-1-one (6e): Isolated as a colourless oil whose data was consistent with the assigned structure. [57] (i) trans-1-(2-Naphthyl)-3-phenylprop-2-en-1-ol (5f): Colourless oil. R f = 0.…”
Section: (G) Trans-3-phenyl-1-(3-pyridyl)prop-2-en-1-ol (5d)mentioning
confidence: 99%
“…[56] 3-Phenyl-1-(2-pyridyl)propan-1-one (6e): Isolated as a colourless oil whose data was consistent with the assigned structure. [57] (i) trans-1-(2-Naphthyl)-3-phenylprop-2-en-1-ol (5f): Colourless oil. R f = 0.…”
Section: (G) Trans-3-phenyl-1-(3-pyridyl)prop-2-en-1-ol (5d)mentioning
confidence: 99%
“…2016, 11,274 -279 www.chemasianj.org nothiophenol and the appropriate aldehyde. [6] 1 Ha nd 13 CNMR spectra were recorded on 300/400 and 100 MHz NMR spectrometers, respectively.T etramethylsilane (TMS) and CDCl 3 were used as internal standards for 1 H( d = 0.0 ppm) and 13 CNMR (d = 77.16 ppm), respectively.M ultiplicities are indicated by s( singlet), d (doublet), t( triplet), q( quartet), p( quintet), h( septet), m( multiplet), and br (broad). The enantiopurity of the chiral compounds was determined by HPLC analysis by using chiral columns with amixture of 2-propanol and hexanes as the eluent.…”
Section: Methodsmentioning
confidence: 99%
“…Based on this demand, the group of Akiyama first introduced benzothiazoline 2 (Figure1)a sanew type of hydrogen donor in the chiral phosphorica cid catalyzed asymmetricr eductiono fk etimines and demonstrated that benzothiazoline 2 was as effective as Hantzsch ester 1 in these transformations. [6][7][8] Since then, several excellent protocols for the chiral phosphoric acid catalyzed asymmetricr eduction of ketimines with benzothiazoline 2 as ah ydrogen donor have been developed. [9][10][11] Most previouse xamples of chiral phosphorica cid catalyzed transfer hydrogenation reactions have been developed by using pregenerated ketimines I,d erived from ketones and panisidine (3), in the presence of ah ydrogen donor.…”
Section: Introductionmentioning
confidence: 99%
“…Although Hantzsch esters have been extensively employed as a hydrogen source, in asymmetric organocatalyzed reactions lately, [6,7] the development of novel hydrogen sources has been expected. We have recently reported that benzothiazoline [8] functioned as a novel reducing agent in the asymmetric transfer hydrogenation of ketimines, [9] giving rise to the corresponding amines with excellent enantioselectivities. As a result of our continuing efforts towards the development of chiral Brønsted acid-catalyzed reactions, [10,11,12] we wish to report herein the phosphoric acid-catalyzed asymmetric transfer hydrogenation of a-imino esters using benzothiazoline as the reducing agent.…”
mentioning
confidence: 99%